The complete chloroplast genome sequence of Iris tectorum. Issue 12 (2nd December 2021) - Feng, Jinglu; Pan, Yunjia; Lin, Yulin; Yao, Hui
Abstract: The complete chloroplast genome sequence of Iris tectorum Maximowicz, assembled with Illumina NovaSeq 6000 system platform sequencing data, was reported. The total length of the chloroplast genome of I. tectorum is 153, 253 bp and its GC content is 37.89%. The complete chloroplast genome has four distinct parts a large single copy region (82, 833 bp), a small single copy region (18, 562 bp), and a pair of inverted repeats (25, 929 bp). The chloroplast genome includes 86 protein-coding genes, 8 rRNAs and 38 tRNAs genes. A phylogenetic tree showed that I. tectorum is close to Iris missouriensis .